Financial Literacy and Financial Capability: Interdependence of Concepts and Possibilities to Form Them in a School Course of Mathematics - Safronova, Tatiana (2020)
Financial literacy and financial capacity of schoolchildren should be developed to meet the requirements of the rapidly developing society and increasingly complicated financial system of the Russian Federation. The authors focused on the financial education of schoolchildren who represent a special target group in financial relations. The main research methods were general scientific methods of cognition: systematization of theoretical and practical material, induction, deduction, comparative analysis, and synthesis. The authors defined the concepts of “financial literacy” and “financial capacity” and substantiated their interdependence using a synergistic approach. The authors considered school math course as a special tool for the formation of financial literacy and financial capacity of schoolchildren, explored the possibility of their development among Russian students in grades 7–9 in the course of algebra, stated the main problems, and formulated conclusions and recommendations.